Specific physical performances among male elite youth soccer players: effect of maturity status - Tounsi, M.; Aouichaoui, C.; Tabka, Z.; Trabelsi, Y. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: There is a lack of studies that investigated the relationship between anthropometric profile, biological maturity and specific soccer performances. Therefore, the aims of the present study were to establish normative data of anthropometric and specific physical performances and to determine the impact age and somatic maturation on young soccer players (U13-U19, n=487). METHODS: Measurements include anthropometric variables to determine the age of peak height velocity (PHV), leg muscle volume (LMV) and soccer specific test (SST); Squat jump (SJ), Counter Movement jump (CMJ), sprint 10 meter (T10m), sprint 20 meter (T20m), sprint 30 meter (T30m) and intermittent-endurance tests. RESULTS: Reference values showed a significant difference between anthropometric variables, LMV and SST according to PHV categories. (M)ANOVA analysis showed a significant age using maturity interaction effect of all anthropometric variables. A significant result was reported in the majority of SST performances for the age, the T10m and for T20m performances. The full model of multiple regressions and the multiple equations was used to determine the best predictors of physical performances according to anthropometric variables. CONCLUSIONS: This study provides normative data for anthropometric characteristics and physical performances according to chronological age (U13-U19) and maturity groups of young soccer players.